How to Improve Patient Care? – An Analysis of Capitation, Fee-for-Service, and Mixed Payment Schemes for Physicians - Jeannette Brosig-Koch; Heike Hennig-Schmidt; Nadja Kairies; Daniel Wiesen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
In recent health care reforms, several countries have replaced pure payment schemes for physicians (fee-for-service, capitation) by so-called mixed payment schemes. Until now it is still an unresolved issue whether patients are really better off after these reforms. In this study we compare the effects resulting from pure and mixed incentives for physicians under controlled laboratory conditions. Subjects in the role of physicians choose the quantity of medical services for different patient types. Real patients gain a monetary benefit from subjects' decisions. Our results reveal that overprovision observed in fee-for-service schemes and underprovision observed in capitation schemes can, in fact, be reduced by mixed incentives. Interestingly, even the presentation of pure incentives as mixed incentives already significantly affects physicians' behavior. Moreover, the mixed payment schemes generally provide a higher benefit-remuneration ratio than the respective pure payment schemes. Our findings provide some valuable insights for designing health care reforms.
Keywords: C91; I11; 330; physician incentive schemes; fee-for-service; capitation; mixed payment; laboratory experiment; presentation effect; benefit-remuneration analysis